Menguak Penerapan Akuntansi pada BUM Desa di Indonesia - Izzalqurny, Tomy Rizky; Shobah, Nurus; Rohmah, Lisya Faidlotur (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2022)
This study aims to explore the application of accounting to previous research on the application of accounting in BUM Desa in Indonesia. This research is also strengthened by examining several BUM Desa in the Jember area to get real information related to how accounting is applied in several regions in Indonesia. This research is an interpretive qualitative research. The focus of this research is BUM Desa. This study uses academic literature and surveys in BUM Desa in Jember Regency. The data used in this study are primary data and also secondary data originating from journals, articles, news, books, websites and resource persons related to Bum Desa accounting. The data analysis technique of this research uses an interactive analysis model. The results of this study are BUM Desa have accounting standards in accordance with government regulations, and there are several BUM Desa that have tried to apply accounting standards and more BUM Desa are unable to apply because of the lack of competent human resources, limited market access, complexity of rules and institutions , support from the village government that has not been optimal, synergies between communities and groups, limited access to capital, low commitment of human resources, unorganized management systems, public accountability and accountability that have not been considered, and there is no awareness of the risks of environmental impacts.